Antagonistic effects of endophytic fungi from Camellia reticulata pedicels on yeasts: implications for antimicrobial mechanism of nectar - Rong Huang; Qingxin Meng; Lijie Xun; Lijie Xun; Xiaoman Wu; Dan Yue; Wenzheng Zhao; Xia Dong; Xueyang Gong; Kun Dong (Frontiers in Plant Science)
Endophytic fungi are extensive in plant tissues and involved in the defense against stress from harmful microbes. The interaction between pedicel endophytic fungi and nectar yeasts is critical for maintaining nectar homeostasis. This study used Camellia reticulata as the research subject. High-throughput sequencing revealed that the community composition of endophytic fungi in the pedicel is dominated by Ascomycota and Basidiomycota. Their abundance varies at different taxonomic levels, showing sample variability. In total, 27 endophytic fungal isolates were isolated and screened from the pedicel under laboratory conditions. They exhibited antagonistic effects against three nectar yeasts (Metschnikowia reukaufii, Cryptococcus laurentii, and Rhodotorula glutinis) and displayed morphological and physiological diversity. The isolates were classified into the phylum Ascomycota and further categorized into the genera Alternaria, Trichoderma, Fusarium, and Dactylaria. The endophytic fungus D23, which effectively antagonizes nectar yeasts, was identified as Alternaria alternata. This fungus produces various secondary metabolites, including antibiotics such as penicillin G, grandiomycin, and cephalosporin C. The metabolic pathways involved include the biosynthesis of plant secondary metabolites, phenylpropanoids, amino acids, nucleotides, and antibiotics. The endophytic fungal community in C. reticulata pedicel is rich and diverse, making it a valuable material for screening antagonistic strains. This study provides a theoretical basis for the antagonistic effects of endophytic fungal metabolites from the pedicel of C. reticulata against nectar yeasts, highlighting their significance in maintaining nectar stability and reproductive fitness in cross-pollinated plants.